Ets-1 Is Essential for Connective Tissue Growth Factor (CTGF/CCN2) Induction by TGF-β1 in Osteoblasts - Geisinger, Max T.; Astaiza, Randy; Butler, Tiffany; Popoff, Steven N.; Planey, Sonia Lobo; Arnott, John A. (PLOS ONE, 2012)
Background Ets-1 controls osteoblast differentiation and bone development; however, its downstream mechanism of action in osteoblasts remains largely undetermined. CCN2 acts as an anabolic growth factor to regulate osteoblast differentiation and function. CCN2 is induced by TGF-β1 and acts as a mediator of TGF-β1 induced matrix production in osteoblasts; however, the molecular mechanisms that control CCN2 induction are poorly understood. In this study, we investigated the role of Ets-1 for CCN2 induction by TGF-β1 in primary osteoblasts. Results We demonstrated that Ets-1 is expressed and induced by TGF-β1 treatment in osteoblasts, and that Ets-1 over-expression induces CCN2 protein expression and promoter activity at a level similar to TGF-β1 treatment alone. Additionally, we found that simultaneous Ets-1 over-expression and TGF-β1 treatment synergize to enhance CCN2 induction, and that CCN2 induction by TGF-β1 treatment was impaired using Ets-1 siRNA, demonstrating the requirement of Ets-1 for CCN2 induction by TGF-β1. Site-directed mutagenesis of eight putative Ets-1 motifs (EBE) in the CCN2 promoter demonstrated that specific EBE sites are required for CCN2 induction, and that mutation of EBE sites in closer proximity to TRE or SBE (two sites previously shown to regulate CCN2 induction by TGF-β1) had a greater effect on CCN2 induction, suggesting potential synergetic interaction among these sites for CCN2 induction. In addition, mutation of EBE sites prevented protein complex binding, and this protein complex formation was also inhibited by addition of Ets-1 antibody or Smad 3 antibody, demonstrating that protein binding to EBE motifs as a result of TGF-β1 treatment require synergy between Ets-1 and Smad 3. Conclusions This study demonstrates that Ets-1 is an essential downstream signaling component for CCN2 induction by TGF-β1 in osteoblasts, and that specific EBE sites in the CCN2 promoter are required for CCN2 promoter transactivation in osteoblasts.